Factors affecting training effectiveness. A study of semiconductor wafer fabrication industry in Malaysia - Lin, Abdullah; Sharif, Mohmad Yazam (2008)
Human Resource Development is one of the key issues for Malaysian companies since the introduction of Human Resource Development Fund (HRDF). This is the fact that rapid changes in the organizations need to develop a more focused and coherent approach to develop and manage people (Kirkpatrick 1979; Senge, 1990). The senior management must consider the important of providing training to the people by understanding and believing that training is one of the important factors in organizational effectiveness. For technological based industry such as in wafer fabrication, the technical training for technical staff is very crucial. Hence, the HR manager must really outline the required training programs focus to the outcomes as well as measuring the effectiveness of the training. Factors that contribute to the training effectiveness must be put into serious consideration so that the amount invested into training is benefited. As such, the objectives of this paper are to review previous literatures and reveal the factors that affect the training effectiveness and outcomes. The scope of this research covers the Semiconductor Wafer Fabrication Companies in Malaysia.